2022
DOI: 10.1186/s13104-022-06235-5
|View full text |Cite
|
Sign up to set email alerts
|

Meat consumption and the risk of general and central obesity: the Shahedieh study

Abstract: Objective This study aimed to investigate the relations of total meat intake and its subtypes, including red and processed meat, white meat, poultry, fish, and organ meat to the risk of general/central obesity. Methods This cross-sectional study included a total of 7312 Iranian adults with the age range of 35–70 years from the Shahedieh cohort study, Yazd, Iran. Dietary intake of subjects was evaluated using a validated 120-item Food Frequency Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…A possible explanation is that meat, egg and dairy products were not finely differentiated in this study to identify the frequency of intake of specific foods among them. If participants consume meat in excess, it can increase the risk of being overweight/obese 51 , 52 . However, the intake of egg and dairy products may moderate poor body weight 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that meat, egg and dairy products were not finely differentiated in this study to identify the frequency of intake of specific foods among them. If participants consume meat in excess, it can increase the risk of being overweight/obese 51 , 52 . However, the intake of egg and dairy products may moderate poor body weight 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 32 Iranian population consumes a large amount of red meat in their usual diet compared to other meats, thus health promotion professionals should consider this fact in their educational interventions. 33 As greater awareness could lead to increased healthy behaviors 32 and thus could go some way towards decreasing the overall burden of diseases such as cancer on the population, health promotion initiatives to educate the public about the association between living a healthy lifestyle and cancer and increasing awareness of these risk factors are essential in ensuring a better understanding of the links between lifestyle and cancer. 20 Most of the participants recognized drinking alcohol as a risk factor which may be consistent with Islamic beliefs in Iranian culture, where drinking alcohol is forbidden.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that some possible functional roles for CAV-1 may be inherited. CAV-1 has also been shown to have a key regulatory function in fat distribution and genetic lipodystrophy in humans (40).A cross-sectional study has reported that processed meat consumption (6.8 g/d) compared to white meat/poultry is more likely to be associated with central obesity (15). In a study, Halkjaer et al showed that a diet rich in processed meat predicts high level of WC among 89 432 men and women from ve countries participating in European Prospective Investigation into Cancer and Nutrition (EPIC) (41).…”
Section: Discussionmentioning
confidence: 99%
“…Various anthropometric indexes may be used to get a top level view of the body composition and health status of the body (13).As an example, BMI, hip circumference (HC), and waist circumference (WC) can be used to measure and monitor obesity (14). So, processed meat intake was associated with central obesity (15). Lipid rafts are lateral assemblies of sphingolipids and cholesterol that feature as structures to which awesome classes of proteins are associated (16).…”
Section: Introductionmentioning
confidence: 99%